2023
DOI: 10.3390/md21070411
|View full text |Cite
|
Sign up to set email alerts
|

Scenedesmus rubescens Heterotrophic Production Strategies for Added Value Biomass

Abstract: Microalgae attract interest worldwide due to their potential for several applications. Scenedesmus is one of the first in vitro cultured algae due to their rapid growth and handling easiness. Within this genus, cells exhibit a highly resistant wall and propagate both auto- and heterotrophically. The main goal of the present work is to find scalable ways to produce a highly concentrated biomass of Scenedesmus rubescens in heterotrophic conditions. Scenedesmus rubescens growth was improved at the lab-scale by 3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Other studies [15,28] have also reported the resistance of S. rubescens to NP exposure. It is possible that the morphological characteristics of this genus, such as its highly resistant cell walls [19], could be among the parameters impacting its behavior. Many species of microalgae are resistant to nanoparticles, especially at low nanoparticle concentrations, and nanoparticles have even been used in order to trigger an increase in biomass concentration and lipid content [29].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies [15,28] have also reported the resistance of S. rubescens to NP exposure. It is possible that the morphological characteristics of this genus, such as its highly resistant cell walls [19], could be among the parameters impacting its behavior. Many species of microalgae are resistant to nanoparticles, especially at low nanoparticle concentrations, and nanoparticles have even been used in order to trigger an increase in biomass concentration and lipid content [29].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, focus was put on Scenedesmus rubescens, a green microalga that is globally present in freshwater and wastewater [19] and has been used in novel industrial applications like biodiesel production [20]. S. rubescens is used as a model species for toxicity since it is found to be resistant to toxic effects induced by the presence of NPs and to exhibit minimal or even no growth inhibition [15].…”
Section: Introductionmentioning
confidence: 99%